(untitled) (Nigerian Journal of Technology, 2025)
Today’s scarcity of fresh water and a rise in polyethylene terephthalate (PET) waste in the environment results from the increase in population. This study examines the impact of utilizing laundry wastewater and PET in concrete production. Laundry wastewater (LWW) and varying percentages of PET (0% to 30%) used as partial replacement for fine aggregate were used to produce 84 concrete cylinders and 84 concrete cubes. The results showed that a 30% PET replacement significantly reduced the workability of concrete by 50% compared to the control mix, and the compaction factor was reduced by 5%. The PET-modified concrete with 5%, 10% and 15 % achieved a target compressive strength of 13.5 N/mm² at 7 days but did not meet the target at 14 and 28 days, unlike the control mix. Prolonged curing time resulted in increased split tensile strength, except for the 5% PET replacement, which showed a decrease at 28 days. Scanning electron microscope (SEM) analysis revealed that the cement and 10% PET aggregates possessed the strongest bond, while the 15% to 30% PET replacement exhibited weak interfacial transition zone (ITZ). Certain properties of the LWW such as increased suspended solids and organic compounds present in detergents and bleach could have reduced the bond strength between cement and aggregates. Regression analysis indicated that the percentage of pulverized PET is a reliable predictor of slump and compressive strength, but less so for tensile strength.